Sediment and geochemistry of bi-gradational contourite sequences from the Gulf of Cadiz - Dorrik A V Stow; Zeinab Smillie; Jonathan Wilkin; Jiawei Pan; Onoriode Esegbue; André Bahr; Emmanuelle Ducassou (PANGAEA, 2024)
The contourite depositional systems at the Gulf of Cadiz during IODP 339 are characterised by the repetition of bi-gradational sequences. These sequences are of an average thickness of 3 m (typical range 0.5-7.5 m) each. The nature of these sequences and the forces that derive such sedimentation patterns are not well understood. The data provided covers two complete bi-gradational sequences from Site U1389. Grain Size fractions from both bulk and carbonate-free analyses are given as well as various grain size parameters are used to decipher the current energy and depositional process. A new approach was used here to assess each size fraction extquotesingles behaviour separately and to used combined sortable silt and fine sand fractions (SSS - sortable silt and sand proxy) to calculate the current speed. In conclusion, aspects of the contourite sequences here justify the dual effects of long-term variation in bottom-current velocity and episodic changes in sediment supply (both lithogenic and biogenic).